A comprehensive study of grid impedance and its reliability effects on variable frequency drive - Ramesh Pandurangan; Kaliannan Palanisamy; Paramasivam Shanmugam (Institute of Advanced Engineering and Science, 2023)
Grid impedance is one of the most important parameters for the satisfactory operation of variable frequency drive (VFD) and their interaction with other utilities connected to the same grid. In this research investigation a new approach to analytical evaluation and verification of grid impedance, and short circuit current is discussed. VFD under identical operating and loading conditions is connected to different grid capacities and configurations, being considered in this investigation. Grid impedance variation in terms of measured or estimated values, due to different grid connectivity affects the commutation of uncontrolled front-end rectifiers. This impacts the nonlinearity of input current wave shape, causing a significant change in current harmonics (THDi) and ripple current of DC link. This paper comprehensively investigates the reduction of DC capacitor lifetime and losses of DC inductor, and diode with various grid capacity and configurations under standard load conditions. High-frequency harmonics impact (2-9 kHz) on DC inductor losses is also analyzed. A VFD of 250 kW is considered for entire practical measurement including distortion effects and MATLAB simulation. This research may give a good insight into the sizing of VFD front-end devices. The reliability impact of VFD is also one of the important outcomes of this research.